Proceedings of the 4th International Conference on Sport Science, Health, and Physical Education (ICSSHPE 2019) 2020
DOI: 10.2991/ahsr.k.200214.034
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Motor Coordination and Physical Activity

Abstract: The research highlights gender differences in gross motor coordination. Preadolescence is the best time for motor skill interventions. Good motor coordination indicates an increased physical activity in children. The purpose of this study was to know the differences of motor coordination and physical activity levels based on gender. School children consisted of 95 males (10.57 years) and 105 females (10.36 years) participated in this study. Weight status, height, and percentage of body fat were objectively mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…In general, boys tend to exhibit higher levels of gross motor skills, such as running and throwing, while girls may excel in fine motor skills, such as handwriting and manipulative tasks [ 13 ]. A significant difference in locomotor skills based on sex has been reported, with the mean motor quotients (KTK) of boys (83.34) being significantly higher than that of girls (72.39) [ 14 ]. However, some studies have found that girls and boys have similar MC levels [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, boys tend to exhibit higher levels of gross motor skills, such as running and throwing, while girls may excel in fine motor skills, such as handwriting and manipulative tasks [ 13 ]. A significant difference in locomotor skills based on sex has been reported, with the mean motor quotients (KTK) of boys (83.34) being significantly higher than that of girls (72.39) [ 14 ]. However, some studies have found that girls and boys have similar MC levels [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%